Im Namen der Dinge - Wörner, David (Basel Schwabe Verlag, 2019)
The main assumption of this book is that Locke s methaphysical considerations spread throughout his works build a coherent metaphysical theory about the essence of things. Contrary to prevalent opinions, Locke thereby proves to be a philosopher who not only criticised the metaphysical systems of the late scholasticism, but also advanced them in a very interesting way.
German
Keywords: Western philosophy: Medieval & Renaissance, c 500 to c 1600; John Locke; metaphysics; essence; identity; philosophy of language